Single sex 'superfish' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The mainstay of small-scale aquaculture for many poor farmers, particularly in Africa and Asia, is the Nile tilapia ( Oreochrornisniloticus). However, because it achieves sexual maturity while still very small, uncontrolled reproduction leads to...